2015
DOI: 10.1104/pp.15.00072
|View full text |Cite
|
Sign up to set email alerts
|

STATE TRANSITION7-Dependent Phosphorylation Is Modulated by Changing Environmental Conditions, and Its Absence Triggers Remodeling of Photosynthetic Protein Complexes

Abstract: In plants and algae, the serine/threonine kinase STN7/STT7, orthologous protein kinases in Chlamydomonas reinhardtii and Arabidopsis (Arabidopsis thaliana), respectively, is an important regulator in acclimation to changing light environments. In this work, we assessed STT7-dependent protein phosphorylation under high light in C. reinhardtii, known to fully induce the expression of LIGHT-HARVESTING COMPLEX STRESS-RELATED PROTEIN3 (LHCSR3) and a nonphotochemical quenching mechanism, in relationship to anoxia wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
106
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(119 citation statements)
references
References 120 publications
(179 reference statements)
11
106
2
Order By: Relevance
“…In addition, Lhcbm4, Lhcbm6, Lhcbm9, Lhcbm11, and CP26 (Lhcb5) have also been shown to undergo phosphorylation during high-light exposure in C. reinhardtii (Turkina et al, 2006;Vener, 2007). However, in addition to the regulation of state transitions, thylakoid protein phosphorylation has been shown to be crucial for the acclimation to high light and anoxia in C. reinhardtii (Bergner et al, 2015) as well as to low light and fluctuating irradiance in Arabidopsis Tikkanen et al, 2006;Grieco et al, 2012). Although the phosphorylation of PSI polypeptides appears to be quite rare (Vener, 2006(Vener, , 2007, PsaD, an extrinsic stroma-exposed protein, was reported as the first phosphorylated PSI subunit in Arabidopsis (Hansson and Vener, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lhcbm4, Lhcbm6, Lhcbm9, Lhcbm11, and CP26 (Lhcb5) have also been shown to undergo phosphorylation during high-light exposure in C. reinhardtii (Turkina et al, 2006;Vener, 2007). However, in addition to the regulation of state transitions, thylakoid protein phosphorylation has been shown to be crucial for the acclimation to high light and anoxia in C. reinhardtii (Bergner et al, 2015) as well as to low light and fluctuating irradiance in Arabidopsis Tikkanen et al, 2006;Grieco et al, 2012). Although the phosphorylation of PSI polypeptides appears to be quite rare (Vener, 2006(Vener, , 2007, PsaD, an extrinsic stroma-exposed protein, was reported as the first phosphorylated PSI subunit in Arabidopsis (Hansson and Vener, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…New data indicated that LHCSR3 also interacts with PSI-LHCI-FNR supercomplexes 26 and that the absence of LHCSR3 accelerates photoinhibition of PSI under conditions where PSI in prone to degradation due to deletion of PGRL1 26 . Now, what determines the interaction of LHCSR3 with other photosynthetic proteins and protein complexes?…”
Section: Lhcsr3 Interacts With Psii and Psimentioning
confidence: 97%
“…In line, all LHCSR protein sequences shown (Figure 2A) possess S and T residues in their N-terminal parts. According to quantitative analyses 60 % of the phosphorylatable residues S 26 , S 28 , T 32 and T 33 are indeed phosphorylated under high light conditions 26 . Notably these N-terminal residues are phosphorylated in an STT7-dependent manner 26 .…”
Section: Lhcsr3 Interacts With Psii and Psimentioning
confidence: 99%
“…S1; Bonente et al, 2011) increased during the light stress. Phosphorylation of LhcSR3 could be involved in the localization of the protein (Allorent et al, 2013;Bergner et al, 2015). Minor and major LHCII antenna can be phosphorylated in Chlamydomonas to move from PSII to PSI during state transition (Iwai et al, 2008;Rochaix, 2014), and this could also be the case for LhcSR3.…”
Section: Psbs and Photoprotectionmentioning
confidence: 99%
“…It has been suggested that LhcSR3 itself is the energy quencher due to its pigment binding ability, the unusual fluorescence properties that show very short lifetime components, and its pH sensitivity (Bonente et al, 2011;Liguori et al, 2013;Tokutsu and Minagawa, 2013). A recent investigation suggests the LhcSR is localized both in grana membranes and stroma lamellae in the moss Physcomitrella patens (Pinnola et al, 2015), and investigations on Chlamydomonas suggest that LhcSR3 can bind both to PSI or PSII depending on illumination conditions (Allorent et al, 2013;Bergner et al, 2015). In contrast to psbS, lhcSR genes are widespread in a many photosynthetic organisms, including green algae, brown algae, diatoms, nonvascular plants, and even some vascular plants (Buchel, 2015).…”
mentioning
confidence: 99%